Composition and Architecture of the Schizosaccharomyces pombe Rad18 (Smc5-6) Complex - Sergeant, John (American Society for Microbiology, 2005)
The rad18 gene of Schizosaccharomyces pombe is an essential gene that is involved in several different DNA repair processes. Rad18 (Smc6) is a member of the structural maintenance of chromosomes (SMC) family and, together with its SMC partner Spr18 (Smc5), forms the core of a high-molecular-weight complex. We show here that both S. pombe and human Smc5 and -6 interact through their hinge domains and that four independent temperature-sensitive mutants of Rad18 (Smc6) are all mutated at the same glycine residue in the hinge region. This mutation abolishes the interactions between the hinge regions of Rad18 (Smc6) and Spr18 (Smc5), as does mutation of a conserved glycine in the hinge region of Spr18 (Smc5). We purified the Smc5-6 complex from S. pombe and identified four non-SMC components, Nse1, Nse2, Nse3, and Rad62. Nse3 is a novel protein which is related to the mammalian MAGE protein family, many members of which are specifically expressed in cancer tissue. In initial steps to understand the architecture of the complex, we identified two subcomplexes containing Rad18-Spr18-Nse2 and Nse1-Nse3-Rad62. The subcomplexes are probably bridged by a weaker interaction between Nse2 and Nse3.